Al ‘Alaqoh Baina Itqoni Al Mufrodat Wa Shihhati Al Qiroah ‘Ala Fahmi Al Kitab “Al Qiroah Al Wafiyyah” Lada At Talamidzi Li Alfashli At Tsaniya ‘Asyaro Bi Ma’hadi Ummu Al Qurro’ Li At Tarbiyyah Al Islamiyyah Boyolali Tahun Pelajaran 2021/2022 - Eko Wahyu Mamad Arfianto; Hafidah (Rayah Al-Islam, 2022)
أهداف هذه الرسالة أولها لمعرفة إتقان المفردات العربية على فهم الكتاب "القراءة الوافية ", وثانيها لمعرفة صحة القراءة على فهم الكتاب "القراءة الوافية ",و ثالثها لوجد العلاقة بين إتقان المفرادات و صحة القراءة على فهم الكتاب "القراءة الوافية " لدى التلاميذ للفصل الثاني عشر بمعهد أمّ القراء للتربية الاسلامية بويولالي العام الدراسي٢٠٢٠–٢٠٢١م. هذه الرسالة هي رسالة كمية ونوعها بحث إرتباطي, تقع بمعهد أمّ القراء للتربية الاسلامية بويولالي, بدأ من شهر مارس إلى مايو 2021. مجتمع البحث هو كل التلاميذ في الصف مع عينة 35 تلاميذا. و أما جمع البينات بطريقة الإختبار الشفوي والتوثيق.و تحليل البينات بإختبار سوى البيانات و مستقيم البيانات . ثم يستخدم الإختبار الفرضية إختبارا f بطريقة الإحصائية.و أما نتيجة الرسالة على نتائج حساب في اختبار العلاقة بالصيغة SPSS فالنتيجة من (f Change) هي 0٬000 وهي أصغر من 0٬05 وفرضيته Ha مقبولة و Ho مفروضة بمعنى هناك العلاقة بين إتقان المفرادات و صحة القراءة على فهم كتاب الوافية في طريقة التعليمية لدى التلاميذ للفصل الثاني عشر بمعهد أمّ القراء للتربية الاسلامية بويولالي العام الدراسي٢٠٢٠–٢٠٢١م. بناء على نتائج حساب في اختبار العلاقة بالصيغة SPSS فالنتيجة من درجة العلاقة (R) هي 0٬782 وهي في فئة 0٬61 -0٬80 علاقتها قوية. بمعنى العلاقة بين إتقان المفرادات و صحة القراءة على فهم كتاب الوافية لها العلاقة القوية The purpose of this study is firstly to determine the mastery of Arabic vocabulary on the understanding of the book "Alqiroah Alwafiyah", and secondly, to determine the validity or correctness of the readings in the book "Alqiroah Alwafiyah", and thirdly to determine the relation between vocabulary mastery and the validity of reading to understanding the book "Alqiroah Alwafiyah" for twelfth graders at the Umm Al-Quraa Islamic Boarding School Boyolali for the 2020-2021 school year.This research is a quantitative research and the type is correlation research, which takes place at the Umm Al-Qura Islamic Boarding School Boyolali, starting from March to May 2021. The research population is all students in the twelfth grade with a sample of 35 students. Meanwhile, for data collection by means of tests and documentation, for classical assumption analysis using normality test and homogeneity test. Then test the final hypothesis using the f-test using statistical methods. As for the results of the calculation on the correlation test using SPSS, the result (F Change) is 0.000 which is smaller than 0.005, then the Ha hypothesis is accepted and Ho is rejected, meaning that there is a relation between vocabulary mastery and reading correctness on the understanding of the Alqiroah Alwafiyah book in second grade students. at the Umm Al-Qura Islamic Boarding School Boyolali for the 2020-2021 Academic Year. Based on the results of calculations on the correlation test using SPSS, the results of the degree of relationship (R) are 0.782 and these results are in the category of 0.61 -0.80, which means there is a strong relationship. This means that there is a relationship between vocabulary mastery and the truth of reading on the understanding of the Alqiroah Alwafiyah book. Which has a strong relationship.